2021
DOI: 10.3390/foods10102367
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of Flavonoids Improves Antimicrobial and Anti-Breast Cancer Activities In Vitro

Abstract: Coarse cereals are rich in flavonoids, which are bioactive substances with a wide range of functions. Biotransformation is considered an emerging approach to methylate flavonoids, displaying prominent regio- and stereoselectivity. In the current study, liquiritigenin, naringenin, and hesperidin flavonoids were biotransformed using O-methyltransferases that were heterologously expressed in Saccharomyces cerevisiae BJ5464-NpgA. Nuclear magnetic resonance (NMR) spectroscopy was used together with high-resolution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…Ma et al [ 170 ] studied the methylation of genes involved in cell cycle control ( p16INK4a or CDKN2A and RASSF1A), and estrogenic transduction ( ER-β or ESR2 ). Hypermethylation of these genes was confirmed in T24 cancer cells, which agrees with other reports on various human cancers [ 169 , 170 , 171 , 172 , 173 , 174 , 175 , 176 , 177 ]. Demethylation of these genes by quercetin restores their transcriptional activity, indicating that p16, RASSF1A, and ER-β are involved in cell growth arrest and apoptosis in T24 cells after quercetin treatment.…”
Section: Molecular and Cellular Targets Of Propolis And Its Flavonoid...supporting
confidence: 91%
See 1 more Smart Citation
“…Ma et al [ 170 ] studied the methylation of genes involved in cell cycle control ( p16INK4a or CDKN2A and RASSF1A), and estrogenic transduction ( ER-β or ESR2 ). Hypermethylation of these genes was confirmed in T24 cancer cells, which agrees with other reports on various human cancers [ 169 , 170 , 171 , 172 , 173 , 174 , 175 , 176 , 177 ]. Demethylation of these genes by quercetin restores their transcriptional activity, indicating that p16, RASSF1A, and ER-β are involved in cell growth arrest and apoptosis in T24 cells after quercetin treatment.…”
Section: Molecular and Cellular Targets Of Propolis And Its Flavonoid...supporting
confidence: 91%
“…According to [ 39 ] and Hao et al [ 171 ], polyphenols, such as quercetin, resveratrol, chrysin, and citrus flavonoids, have the ability to modify gut microflora and improve an imbalance of intestinal microbiota, thereby promoting gut health. Intestinal polyphenol metabolites are capable of modifying the activity of enzymes important for the detoxification process and inflammation [ 3 , 13 , 49 , 75 , 129 , 170 ].…”
Section: Antitumor Activity Of Propolis and Its Polyphenolic/flavonoi...mentioning
confidence: 99%
“…[ 5 , 6 ]. Hesperidin and hesperetin have been documented to exhibit a wide range of pharmacological properties, including anti-inflammatory, antimicrobial, anticarcinogenic, antithrombotic and anti-viral activity [ 7 , 8 , 9 , 10 , 11 ]. Recently, it has been demonstrated that hesperidin has a beneficial effect on the skin [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is a need to develop efficient methods to produce biologically active compounds, including various glycosylated polyphenolic compounds. In this regard, the biotransformation has been highlighted as an alternative method to produce biological active compounds, and many researchers have contributed their efforts [23]. Biotransformation is the process of converting substrates to products using biological systems.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is no need to supply these factors for the biotransformation by microorganisms. Compared to chemical synthesis, biotransformation has advantages in that the reaction conditions are simple, safe, and generate less contaminants [23][24][25]. For these reasons, biotransformation has been successfully applied in the large-scale industrial production of biologically active materials for new drugs and cosmetics [26,27].…”
Section: Introductionmentioning
confidence: 99%